Esercizi spirituali, "horologia" e mistica protocollare. Da Ignacio di Loyola a Franz Kafka - Cuozzo, Gianluca (Filosofia, 2017)
Bureaucracy works through a thorough codification of collective consciousness. As the first step toward this enslavement of the spirit, the time dimension of human existence is deprived of its original meaning, and strictly regimented – as Kafka asserted following Arthur Holitscher’s argument in Amerika Heute und Morgen. Accordingly, law rises in this void as mere form without a content, a phenomenon which finds its equivalent in the subject’s fall into a state of inability. Loyola’s Spiritual Exercises introduce a strict discipline of existential time from a quantitative point of view, a preamble to the process of mechanization of life. From this vision, bureaucratic capitalism inherits only pervasive feelings of guilt, without any hopes for salvation. Kafka’s Metamorphosis is the heir to this degeneration of life into a mechanism from hell, in which any gesture, in its endless repetitiousness, generates its own punishment.